Gene expression and biochemical profiling in the mitigation of heat stress in common bean using Bacillus subtilis - Lima, B. C.; Cruz, T. R. [UNESP]; Ribas, A. F.; Santos, T. B.; Cacefo, V.; Araujo, F. F. (Institute of Experimental Botany, 2023)
The present work aimed to evaluate the effect of heat stress on common bean (Phaseolus vulgaris L.) genotypes during the reproductive phase as a function of the inoculation of plants with Bacillus subtilis. The treatments were established by inoculating two strains of B. subtilis (AP-3 and AP-12) and a control. The plants were subjected to heat stress when they reached the reproductive stage, with an increase in temperature to 28/33°C. The duration of the stress period was ten days. Flowering, biochemical, and gene expression evaluations were performed. There was the interaction of B. subtilis AP-3 with the bean cultivar IAC-Imperador, reducing flower abortion, promoting the formation of new flower buds, and increasing the content of proline and guaiacol peroxidase activity in plant tissues. However, there was a reduction of transcription of genes encoding the 1-carboxylic acid-1aminocyclopropane oxidase and ethylene response factors and an increase of the Δ1-pyrroline-5-carboxylate synthetase1 gene. These results suggest that B. subtilis may modulate some metabolic pathways in response to high-temperature stress during the reproductive phase of the common bean. This also confirms that Bacillus strains represent a useful option to moderate abiotic stresses.
Keywords: gene expression; Phaseolus vulgaris L; plant growth-promoting rhizobacteria; stress tolerance